2022
DOI: 10.1098/rstb.2021.0125
|View full text |Cite
|
Sign up to set email alerts
|

Institutionalizing the Blue Economy: an examination of variations and consistencies among Commonwealth countries

Abstract: The Blue Economy is a catch all term that is used to describe a wide variety of development approaches and priorities in the ocean and coastal areas. A number of distinct, and sometimes conflicting discourses have emerged in relation to the Blue Economy, which are distinguished by the degree to which they prioritize different development objectives. This paper explores the range of Blue Economy interpretations, governance strategies and implementation approaches that exist across Commonwealth countries. Key Bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…Other methodological tools have been developed to assess other aspects of the blue economy. For example, Voyer et al (2022) looked at the level of blue economy institutionalization in Commonwealth countries. Their work examined different facets of the blue economy in operation to from an understanding of governance, as well as priority sectors throughout the Commonwealth with a focus on alignment to SDGs and the Commonwealth Blue Charter.…”
Section: Current Methods To Assess Blue Economy Developmentmentioning
confidence: 99%
See 3 more Smart Citations
“…Other methodological tools have been developed to assess other aspects of the blue economy. For example, Voyer et al (2022) looked at the level of blue economy institutionalization in Commonwealth countries. Their work examined different facets of the blue economy in operation to from an understanding of governance, as well as priority sectors throughout the Commonwealth with a focus on alignment to SDGs and the Commonwealth Blue Charter.…”
Section: Current Methods To Assess Blue Economy Developmentmentioning
confidence: 99%
“…Building on the previous analysis of blue economy development in Commonwealth countries by Voyer et al (2022), as well as the work by Adrianto (2022) and Cisneros-Montemayor et al (2021), we developed a methodology by which to assess and categorize the level of blue economy development at a national level. This methodology relies on two schemes: the development of a global blue economy database; and the creation of a categorization tool.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, there are few examples of national adoption of the blue economy as a transformational approach for the sustainable development of the ocean. A recent analysis of how blue economy has been enacted and governed across Commonwealth countries shows an array of plans and policies at different stages of development and implementation and institutional arrangements (Voyer et al, 2022). This review found that in practice, the blue economy may succeed if a more integrated approach to sectoral management is developed; however, there was less evidence that it was successful in driving integration of social, economic, and environmental objectives, with particularly limited engagement with equity objectives across many countries.…”
Section: Introductionmentioning
confidence: 99%